Efficiency centric reliable communication mechanism for wireless sensor networks - ZHANG Xi-yuan1; ZHAO Hai1; SUN Pei-gang1; XU Jiu-qiang1; ZHU Jian1 (Tongxin xuebao)
Reliable transfer mechanism was needed for wireless sensor network’s communication link to ensure end-to-end reliability. After pointing out that traditional MAC protocol can not provide energy efficient reliable transfer, a new group-based acknowledgement mechanism, which was efficiency centric, was brought forward. And then surround- ing the EPB of communication link, mathematic method was adopted to compare the performance between the new and traditional mechanisms. And the theory analysis proves that the new mechanism can reduce energy cost obviously. Meanwhile, the new mechanism requires a smaller buffer for sensor nodes through overhearing technique. Finally, per- formance of the group-based acknowledgement mechanism has been tested through experiment on Micaz platform, which proves that this mechanism is more suitable for the application of resource limited sensor networks.